2018
DOI: 10.1002/art.40410
|View full text |Cite
|
Sign up to set email alerts
|

Switched Memory B Cells Are Increased in Oligoarticular and Polyarticular Juvenile Idiopathic Arthritis and Their Change Over Time Is Related to Response to Tumor Necrosis Factor Inhibitors

Abstract: Switched memory B cells expand during the disease course at a faster rate in JIA patients than in healthy children. This increase is more evident in patients with early-onset JIA. TNFi treatment inhibits this increase in patients who achieve and maintain remission, but not in those with active disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 27 publications
2
18
1
1
Order By: Relevance
“…Although age-related and disease course associated changes in memory B cells have been reported ( 29 , 30 ) we did not observe a correlation between memory or naïve B cell population and age or disease duration ( Supplementary Figure S2 ). We observed a relatively higher estimated memory B cell fraction in JIA cases with late-onset uveitis, but this difference was not statistically significant ( P = 0.08) ( Supplementary Figure S3 ).…”
Section: Resultscontrasting
confidence: 59%
See 3 more Smart Citations
“…Although age-related and disease course associated changes in memory B cells have been reported ( 29 , 30 ) we did not observe a correlation between memory or naïve B cell population and age or disease duration ( Supplementary Figure S2 ). We observed a relatively higher estimated memory B cell fraction in JIA cases with late-onset uveitis, but this difference was not statistically significant ( P = 0.08) ( Supplementary Figure S3 ).…”
Section: Resultscontrasting
confidence: 59%
“…Some cases in this study used methotrexate. Although previous studies have shown that IgG-positive memory B cell frequency is increased in JIA patients treated with methotrexate, the absolute numbers of memory B cells are not affected (38), nor did methotrexate halt the progressive increase of memory B cells in early onset JIA (29). Also here, we would like to emphasize that conclusive data on changes in the composition of B cell subsets warrants further in-depth cytometry analysis ideally at different time points in cohorts of JIA cases with significant ophthalmological follow-up.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Recent studies have suggested that B cells may have a role in these disorders. For example, B cell-related genes were up-regulated in JIA patients [ 4 ], and memory B cells were increased in oligoarticular and polyarticular JIA patients [ 5 ].…”
Section: Introductionmentioning
confidence: 99%